An unusual case of duplicated popliteal vein and its effect on the diagnosis of deep vein thrombosis - P, Ashwini Aithal; Kumar, Naveen; B, Satheesha Nayak; Shetty, Surekha D; Patil, Jyothsna; S, Swamy Ravindra (Bangladesh Journal of Medical Science, 2017)
Background: We report in here a very unusual appearance of a duplicated popliteal vein found in a male cadaver. Popliteal vein is usually a single vein present deep in the popliteal fossa which is formed by the union of venae comitantes of the anterior and posterior tibial arteries. Methods: Anatomical variation in the lower extremity was identified during routine dissection of human cadaver. Result: We noted the presence of unilateral doublepopliteal veins which were formed at the lower end of popliteal fossa. Both the veins were found closely related to the popliteal artery and both of them received tributaries. In the adductor canal both the popliteal veins joined to form the femoral vein. Conclusion: It has been believed that such venous variations in lower limbs have important implications for diagnostic ultrasonography imaging in cases which are suspected with deep vein thrombosis. Thus this case reported in here is very helpful for surgeons for proper diagnosis and management of deep vein thrombosis and also to radiologists to aid in the interpretation of venograms. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.150-153